2020
DOI: 10.13057/biodiv/d210812
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, biomass, and carbon stock of understorey plants in the rubber agroforestry and rubber monoculture systems in Central Tapanuli District, North Sumatra, Indonesia

Abstract: Abstract. Muhdi, Hanafiah DS, Butar-Butar RD. 2020. Diversity, biomass, and carbon stock of understorey plants in the rubber agroforestry and rubber monoculture systems in Central Tapanuli District, North Sumatra, Indonesia. Biodiversitas 21: 3508-3518. Understorey vegetation plays an important role in carbon stock in forest. The objectives of the research were to identify the species of understorey, to find out the amount of carbon stored in the understorey, and to compare the understorey carbon stocks in rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Another study at Central Tapanuli also observed the diversity of understory plants in 2 management, i.e., agroforestry and monoculture. The result was classified as moderate (2.62 and 2.35, respectively; Muhdi et al 2020). This previous study held two plots with two repetitions: 20x20 m for the tree and 1x1 m for the seedling.…”
Section: Methodsmentioning
confidence: 99%
“…Another study at Central Tapanuli also observed the diversity of understory plants in 2 management, i.e., agroforestry and monoculture. The result was classified as moderate (2.62 and 2.35, respectively; Muhdi et al 2020). This previous study held two plots with two repetitions: 20x20 m for the tree and 1x1 m for the seedling.…”
Section: Methodsmentioning
confidence: 99%
“…Vice versa, the largest carbon sequestration can be contributed by the restoration of degraded and deforested lands to form primary and secondary forests (Basyuni et al 2021). Rubber agroforest also contains biodiversity since it will develop into a secondary forest despite the vegetation community and biomass being dominated by rubber trees (Beukema et al 2007;Muhdi et al 2020;Siswo et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Böhnert et al (2016) revealed that jungle rubber provides a favorable environment for epiphytic species diversity, on par with forests. Furthermore, Muhdi et al (2020) found that jungle rubber has higher species richness than monoculture rubber. Unfortunately, these reports are generally limited to quantitative values of diversity such as species richness, diversity index, dominance index and importance value.…”
Section: Introductionmentioning
confidence: 99%